The Effectiveness of Cognitive Restructuring Techniques in Reducing Academic Procrastination among Junior High School Students - Epin Candra Buana; Ebtaniz Zulwidyaningtyas (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Academic procrastination is a significant problem experienced by many junior high school students. This behavior often leads to decreased productivity in completing academic assignments and can negatively impact students' overall academic performance. One of the main causes of procrastination is the presence of negative thought patterns related to self-doubt, fear of failure, and low motivation. Objective: The objective of this study is to examine the effectiveness of cognitive restructuring techniques in reducing academic procrastination among junior high school students by helping them replace negative thought patterns with more positive and productive ones. Method: This research employed a mixed-method approach using a Sequential Explanatory design, which integrates quantitative and qualitative methods. The study was conducted in 2023 at SMP Negeri 1 Kepung. Data were collected through a questionnaire, and the quantitative data were analyzed using the t-test to determine the significance of the intervention. Result: The results indicated that cognitive restructuring techniques delivered through group counseling were effective in reducing academic procrastination behavior in students. The intervention led to measurable improvements in students' ability to manage their academic tasks more responsibly. Conclusion: Cognitive restructuring is a beneficial technique for addressing academic procrastination. By modifying students' maladaptive thoughts, it contributes to improved learning behavior and increased academic engagement. Contribution: This study contributes to the field of guidance and counseling by providing empirical evidence on the effectiveness of cognitive restructuring techniques in a group counseling setting. It offers practical implications for school counselors and educators in developing strategies to address academic procrastination among junior high school students.